1991
DOI: 10.1073/pnas.88.4.1110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the intermediate allosteric species in human hemoglobin reveals a molecular code for cooperative switching.

Abstract: The 10 ligation species of human cyanomethemoglobin were previously found to distribute into three discrete cooperative free energy levels according to a combinatorial code (i.e., dependent on both the number and configuration of ligated subunits). Analysis of this distribution showed that the hemoglobin tetramer occupies a third allosteric state in addition to those of the unlgated (1) ates plus the 2 end-state species) are shown in Fig. 1 for conditions of pH 7.4 and 21.50C (13,15). The initial determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
5

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 27 publications
6
54
5
Order By: Relevance
“…7), indicating that Asymmetric effect of single desArg modification at the first ligand binding step. The first CNmet ligand, denoted as X, binds to either ␣-(shown) or ␤-subunit in wild-type Hb (gray subunits) with a ⌬G c penalty of 3.0 Ϯ 0.2 kcal͞mol at pH 7.4 and 21.5°C (38). When both ␣141Arg residues are removed (green subunits), effectively eliminating ␣ 1 -␣ 2 contacts between the two dimers, the penalty is reduced to 1.0 Ϯ 0.2 kcal͞mol.…”
Section: Resultsmentioning
confidence: 99%
“…7), indicating that Asymmetric effect of single desArg modification at the first ligand binding step. The first CNmet ligand, denoted as X, binds to either ␣-(shown) or ␤-subunit in wild-type Hb (gray subunits) with a ⌬G c penalty of 3.0 Ϯ 0.2 kcal͞mol at pH 7.4 and 21.5°C (38). When both ␣141Arg residues are removed (green subunits), effectively eliminating ␣ 1 -␣ 2 contacts between the two dimers, the penalty is reduced to 1.0 Ϯ 0.2 kcal͞mol.…”
Section: Resultsmentioning
confidence: 99%
“…For the Fe/Fe + data, the calculated ratio of oxygen affinities is 237 (ZZG of 3.2 kcal/mol); this value was apparently rounded off to 3 kcal/mol when reported as a factor of 170 [3,94]. Application of this definition (pathway 01-11-21) does not seem to have been uniformly employed; the origin of the reported value of 40 for the Fe/Fe-O 2 (equivalent to the Zn/Fe) is not obvious; Huang et al [34] indicated an energy of 2.2 kcalmol (factor of 40), but this value is only the ZG between 11 and 21 tetramers. It was pointed out (by N. Shibayama) that the correct value based on the reported free energies is [(14.4− 11.6)− (11.6−9.4)]= 0.6 kcal/mol or a factor of 2.8, which is consistent with the simple two-state model.…”
Section: Discussionmentioning
confidence: 99%
“…The original evidence for this preferred ligation pathway was the hyper (170-fold) stability of (␣ ϩCNϪ ␤ ϩCNϪ )(␣␤) relative to the other three doubly liganded species (7)(8)(9). However, this evidence has been proven to be an artifact arising from valency exchange between the deoxy and cyanometheme sites during the long deoxy incubation that had been used routinely in the laboratory of Ackers (11,12).…”
Section: O 2 Equilibrium Properties Of [␣(Fe)␤(fe)][␣(zn)␤(zn)]-di-mentioning
confidence: 99%
“…a 170-fold affinity change). Subsequently, the effects of pH, temperature, and single-site mutations on the dimer-tetramer equilibrium of (␣ ϩCNϪ ␤ ϩCNϪ )(␣␤) were studied (7,9,10). It was suggested that this key intermediate assumes a form of the deoxy-Tquaternary structure as judged from the nature of the dimerdimer interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation